Graphene quantum dots conjugated albumin nanoparticles for targeted drug delivery and imaging of pancreatic cancer - Nigam, Preeti; Waghmode, Shobha; Louis, Michelle; Wangnoo, Shishanka; Chavan, Pooja; Sarkar, Dhiman (Journal of Materials Chemistry B, 2014)
Pancreatic cancer is considered to be the deadliest of all cancers due to its poor prognosis and resistance to conventional therapies. In this study, the potential of hyaluronic acid functionalized and green fluorescent graphene quantum dot (GQD)-labeled human serum albumin nanoparticles for pancreatic cancer specific drug delivery and bioimaging was explored. GQDs with tunable fluorescence properties and biocompatibility have attracted much more interest in recent years as compared to their metal semiconductor counterparts. We adopted lawsone (2-hydroxy-1,4-naphthoquinone) as a novel reducing agent for the synthesis of quantum dots and, in addition to excellent fluorescence of the synthesized GQDs, a good quantum yield of similar to 14% was also obtained. Gemcitabine, the most preferred drug for pancreatic cancer treatment, was encapsulated in albumin nanoparticles, and it was observed that our nanoformulation significantly enhanced the bioavailability and sustained release property of the drug to pancreatic cancer cells in vitro. Moreover, the GQD-mediated bioimaging was excellent and enhanced the efficacy of our system as a drug delivery vehicle.

Carboxymethyl cellulose based multifunctional targeted drug delivery platform for pancreatic cancer: nanotheranostic potential and biocompatibility analysis - Joshi, Preeti Nigam; Wangnoo, Shishanka; Louis, Michelle (World Journal of Pharmaceutical Sciences, 2015)